Identifikasi Tingkat Kerentanan Masyarakat Terhadap Kebakaran Hutan dan lahan di Desa Tumbang Nusa - Ise Afitah (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
Identification of Community Vulnerability to Forest and Land Fires in Tumbang Nusa Village. Lecturer, Forestry Study Program, Faculty of Agriculture and Forestry, Muhammadiyah University of Palangkaraya. The Tumbang Nusa Village area is characterized by peatlands that are prone to fire. Coupled with community activities that depend on land use, the risk of forest and land fires is relatively high and has a significant impact on social, economic, and public health. Forest and land fire control is necessary, one of which is prevention. This study aims to identify the level of community vulnerability to forest and land fires in Tumbang Nusa Village, Central Kalimantan. Vulnerability analysis was conducted based on the components of exposure, sensitivity, and adaptive capacity of the community using qualitative and quantitative descriptive approaches. The results indicate that the community's level of vulnerability is moderate to high, influenced by high exposure due to the proximity of settlements to peatlands, high socioeconomic sensitivity, and low adaptive capacity. Biophysical, social, economic, and institutional factors are the main determinants of vulnerability. Therefore, increasing community adaptive capacity through institutional strengthening, increased knowledge, and the provision of firefighting infrastructure is a key strategy for reducing the risk of forest and land fires.